2006
DOI: 10.1007/s00421-006-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation, EMG and position sense during computer mouse work. Impact of active versus passive pauses

Abstract: We investigated the effects of active versus passive pauses implemented during computer mouse work on muscle oxygenation and EMG of the forearm extensor carpi radialis muscle, and on wrist position sense. Fifteen healthy female subjects (age: 19-24 years) performed a 60-min mouse-operated computer task, divided into three 20 min periods, on two occasions separated by 3-6 days. On one occasion a passive pause (subjects resting) was implemented at the end of each 20-min period, and on another occasion an active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 28 publications
5
35
1
Order By: Relevance
“…In addition, Lacaze, Sacco Ide, Rocha, et al reported that active breaks with stretching and joint mobilization reduced muscle discomfort significantly better than passive breaks [41]. The positive effect of dynamic contractions on a lower level of discomfort after rest-break intervention could result from increased muscle oxygenation [28].…”
Section: Muscle Discomfortmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Lacaze, Sacco Ide, Rocha, et al reported that active breaks with stretching and joint mobilization reduced muscle discomfort significantly better than passive breaks [41]. The positive effect of dynamic contractions on a lower level of discomfort after rest-break intervention could result from increased muscle oxygenation [28].…”
Section: Muscle Discomfortmentioning
confidence: 99%
“…Individual operators can perform some physical activity, exercise or change their posture during the breaks [26]. Some authors use the word "pause" instead of rest break or break [27,28]. Pauses during computer work tasks can be passive or active.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing use of computers is believed to have caused computer-related disorders (CRDs), such as eye fatigue, stiff shoulders, upper extremity pain, lower back pain, and mental stress [3,4]. Factors that can contribute to these conditions include the setting of the computer screen, which affects working posture [5], operating the computer for extended periods [6][7][8], and tasks that require repetitive and monotonous motions [9][10][11][12]. Additionally, mental stress levels are known to increase with the duration of computer-related tasks.…”
Section: Introductionmentioning
confidence: 99%